EFISIENKAH BELANJA PENDIDIKAN KABUPATEN? - IKIP PGRI Semarang, Sunandar Program Pascasarjana MP; IKIP PGRI Semarang, Nurkolis Program Pascasarjana MP (Jurnal Manajemen Pendidikan, 2012)
Abstract. The focus of this research is the efficiency of education expenditure, education inputs, educataions outputs, and education outcomes on basic education. Data collection use documents as a major source, data analisys tecknique use combination of quantitative and descriptive qualitative. This reasearch located in Wonosobo District,2011. Research finding shows that for four years recently education expenditure above 20 %. For 95 % allocated to indirect expenditure as of employee salary. The inputs of basic education especially provision of schools and classrooms are exceeded the need, but the availability of good classrooms and urinoir are less than enough. Inputs of class-teacher and subject matter teacher are exceeded the need but compolsary hours of teaching low. Teacher qualification are under the standard.Outputs of education are good according to the repetition rate, drop out rate, and school completion. Outcomes of education are good according to gross participation rate, net participation rate, and score of national exam. Itâs concluded that education efficiency has not happen yet since there is inefficiency in salary. Itâs recomended to reorganize teachers and administrators. Abstrak: Fokus penelitian ini adalah efisiensi belanja pendidikan, input pendidikan, output pendidikan dan outcome pendidikan dasar. Teknik pengumpulan data dengan studi dokumentasi sementara, teknik analisis data secara deskriptif kuantitatif-kualitatif. Penelitian berlokasi di Kabupaten Wonosobo tahun 2011. Hasil penelitian menunjukkan bahwa selama empat tahun terakhir belanja pendidikan termasuk gaji telah melebihi 20 % dari APBD. Sebesar 95 % belanja pendidikan untuk belanja tidak langsung berupa gaji. Input pendidikan dasar dilihat dari jumlah sekolah dan ruang kelas terdapat kelebihan. Tetapi dilihat dari jumlah ruang kelas yang layak pakai dan jumlah WC masih ada kekurangan. Input tenaga kependidikan baik guru kelas dan guru mata pelajaran juga mengalami kelebihan, namun beban mengajar dan kualifikasi akademik pendidik masih banyak yang belum memenuhi standar. Output pendidikan dasar sudah baik dilihat dari angka tinggal kelas, angka putus sekolah, dan angka ketidaklulusan. Outcome pendidikan dasar juga sudah baik dilihat dari APK, APM, dan Nilai UN yang ketiganya menunjukkan kecenderungan meningkat.Â Dapat disimpulkan bahwa belanja pendidikan tidak efisiensi. Dengan demikian direkomendasikan untuk melakukan penataanÂ ulang pendidik dan tenaga kependidikan. Keywords: efficiency of education expenditure, education inputs, outputs, outcomes. Â